Ecoterrorism and Cyberattacks vs. Critical Infrastructure: Counterintelligence and Security Aspects - Živaljević, Dragan; Gavrić, Nevena (NBP. Nauka, bezbednosti, policija, 2026)
Critical infrastructure encompasses systems and resources essential to the functioning of the state and its protection consequently stands at the pinnacle of counterintelligence and security priorities. Amid increasingly intensive and complex forms of hybrid threats, the vulnerability of such systems becomes more pronounced—particularly in the domains of cyber-attacks and eco-terrorist acts, as emergent forms of asymmetric threats. Of particular concern is the employment of sophisticated methods of espionage, cyber intrusions and subversive activities, all of which necessitate a strategically oriented and integrated counterintelligence response. In addition to conventional and digital security risks, growing attention must be directed towards the phenomenon of eco-terrorism—that is, the activities of radical environmental groups which, under the guise of environmental protection, carry out attacks targeting infrastructure of vital importance. Cyber threats, including intrusions into operational networks, data destruction and manipulation of control systems, constitute a parallel dimension of security vulnerability, one that challenges the response capacity of traditional protection systems. This paper examines the intersection between eco-terrorism, cyber-attacks and the counterintelligence protection of critical infrastructure, with a particular focus on identifying vulnerabilities, evaluating the effectiveness of existing measures and analysing the role of institutional actors in the prevention, detection and response to such threats. Special attention is paid to the challenges of intersectoral coordination and the pressing need to improve both national and international regulatory and operational frameworks. Drawing upon an analysis of current security strategies and selected case studies, the paper argues that the effective safeguarding of critical infrastructure is achievable solely through a multidisciplinary and comprehensive approach—one that integrates counterintelligence capabilities, technological innovation and international cooperation. The findings of the research offer concrete recommendations for the reform and enhancement of legal and institutional mechanisms, with an emphasis on proactive engagement, situational awareness and adaptive crisis response to threats emerging from eco-terrorist and cyber domains. The contribution of this study lies in its critical examination of the security aspects of contemporary threats to critical infrastructure, offering insights relevant both to the academic community and to decision-makers engaged in the formulation of national and international security policy.